Macam-Macam Ruang Lingkup Administrasi Pendidikan Yang Meliputi Bidang Tata Usaha, Bidang Personalia Murid Dan Guru, Bidang Supervisi (Pengawasan), Bidang Pelaksanaan, Dan Bidang Pembinaan - Nurhayati, Dinda Siti; Hasanah Usnur, Uswatun (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
In educational administer jation there are various scopes which are usually called the scope of educational administration. The scope of educational administration includes the field of administration, student personnel, teacher personnel, supervision, implementation and coaching. This journal uses a literature approach method that uses books, journals and other websites related to the scope of administration. The results of this journal are the scope which covers several specific fields which are very important and interrelated with each other, where these fields can facilitate the educational process both in terms of administration and teaching and learning that occur in the school environment.